2018
DOI: 10.1093/jas/sky244
|View full text |Cite
|
Sign up to set email alerts
|

Performance-enhancing technologies for steers grazing tall fescue pastures with varying levels of toxicity1

Abstract: The objective of this study was to evaluate a combination of best management practices strategy for steer calves grazing tall fescue pastures with a range of toxicity. The experiment was conducted over two grazing seasons (fall 2015 for 91 days and spring 2016 for 84 days). Steers (n = 80 within season, BW = 197.0 ± 15.43 kg [fall] and 116.9 ± 4.88 [spring]) were stocked at 2.45 and 4.1 calves/hectare in fall and spring, respectively, to 16 pastures with varying levels of toxicity based on interim ergovaline (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…This effect may have caused the reduction in steer performance during the final 28 days of the experiment; however, untangling the confounded effects of declining forage quality and increasing alkaloid concentration and environmental stress on cattle ADG in a pasture setting is difficult. Diaz et al (2018) found as ergovaline concentration in the diet increased, cattle ADG decreased, which matches what was reported in the current experiment. Reduced performance in period 2 could be attributed to declining forage quality.…”
Section: Steer Performancesupporting
confidence: 92%
See 2 more Smart Citations
“…This effect may have caused the reduction in steer performance during the final 28 days of the experiment; however, untangling the confounded effects of declining forage quality and increasing alkaloid concentration and environmental stress on cattle ADG in a pasture setting is difficult. Diaz et al (2018) found as ergovaline concentration in the diet increased, cattle ADG decreased, which matches what was reported in the current experiment. Reduced performance in period 2 could be attributed to declining forage quality.…”
Section: Steer Performancesupporting
confidence: 92%
“…Pastures within the experiment expressed a variety of ergovaline concentrations throughout; therefore, the authors regressed average daily gain against pasture ergovaline concentration. Diaz et al (2018) reported the y-intercept of the two treatments was similar; however, each treatment expressed different slopes as the ergovaline concentration increased. For the mineral only treatment group, there was a linear decrease in ADG as ergovaline concentrations increased.…”
Section: Section 5 -Stocker Cattle Management On Tall Fescuementioning
confidence: 93%
See 1 more Smart Citation